Comparative legal study of non-performance of the obligations under the laws of France, Germany and Ukraine - Martsenko, Natalia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
Relevance of the research topic. Throughout the history of contract law, parties to a contract have faced the problem of non-performance or improper performance of a contract for reasons that may or may not depend on their will. Despite this, freedom of contract and proper performance of contractual obligations are one of the main principles of both Ukrainian and foreign contract law. Impossibility of performance of the obligation may occur even at the stage of concluding the contract, where it may be exposed to various risks, including force majeure circumstances. Due to their unpredictability, such events cannot always be foreseen in the contract. Therefore, in practice, a number of difficult issues arise related to compliance with the conditions of proper performance of the contract and compensation for the damage caused. Non-performance, improper performance or impossibility of performance of the contract cover an extremely wide range of issues, which in turn became the basis for the formation of various legal doctrines, including frustration, impossibility, force majeure, impracticability, hardship, etc. Clarifying the influence of the relevant circumstances on non-performance of the contract and their legal consequences in different legal systems will help to assess the effectiveness of legal regulation and outline directions for its improvement. The purpose of this study is to determine the peculiarities of the legal regulation of non-performance and improper performance of contractual obligations and to carry out a comparative legal analysis of the legal basis in order to borrow the positive experience of foreign countries. Results of the research. The article examines the concept and essence of non-performance and improper performance of an obligation in the civil law of France, Germany and Ukraine. The peculiarities of the concept of non-performance and improper performance of an obligation in the law of foreign countries were studied and their legal consequences for the parties to the contract were analyzed. Reasons due to which non-performance and improper performance of the obligation may occur are considered. Peculiarities of legal regulation in the event of circumstances beyond the control of the contracting parties, which make it impossible to fulfill the contractual obligation, have been studied. The position is advocated that the quality of the presentation of the content of the contract will guarantee compensation to the parties in case of non-performance or improper performance of the obligation.